Job competition and the wage curve - Simonetta Longhi (Institute for the Study of Labor (IZA), 2010)
The wage curve literature consistently finds a negative relationship between regional unemployment rates and regional wages; the most widely accepted theoretical explanations interpret the unemployment rate as a measure of job competition. This paper proposes new ways of measuring job competition, alternative to the unemployment rate, and finds that the negative relationship still holds when job competition is measured following the job search literature. While for men the wage impact of the theoretically-based measures of job competition is rather similar to the wage impact of the unemployment rate, for women the difference is substantial.
Keywords: J31; R23; 330; Wage curve; unemployment; on-the-job search; Lohnkurve; Regionale Arbeitslosigkeit; Regionale Lohnstruktur; Arbeitsuche; Wettbewerb; Messung; Schätzung; Großbritannien